SmTAL-9, a Member of the Schistosoma mansoni Tegument Allergen-Like Family, Is Important for Parasite Survival and a Putative Target for Drug/Vaccine Development - Bernardes, Wilma Patrícia de Oliveira Santos; Dutra, Isabela Thamara Xavier; da Silva-Pereira, Rosiane Aparecida; Mourão, Marina Moraes; Fonseca, Cristina Toscano (Frontiers in Immunology, 2022)
The tegument of Schistosoma mansoni is involved in essential functions for parasite survival and is known to stimulate immune responses in pre-clinical vaccine trials. SmTAL-9, a member of the tegument-allergen-like (TAL) family, is one of the components of the tegument of schistosomula recognized by sera from immunized and protected mice. In this work, we assessed the role of SmTAL-9 in parasite survival using the RNAi approach. Also, we cloned and expressed a recombinant form of SmTAL-9 and evaluated its ability to induce protection in mice. Smtal-9 knockdown did not impact parasite survival in vitro, but significantly decreased schistosomula size. Additionally, significant reduction in both parasite and egg burdens were observed in mice inoculated with smtal-9-knockdown schistosomula. Immunization using the SmTAL-9 as an antigen conferred partial protection against challenge infection. Overall, our results indicate that SmTAL-9 is a candidate target for drug and/or vaccine development due to its important role in parasite biology and survival.